Australian vocational education and training : research messages - National Centre for Vocational Education Research (Australia) (Adelaide, S. Aust. : National Centre for Vocational Education Research, 2005)
Collection of summaries on all research projects published or completed by the National Centre for Vocational Education Research during the year with details of how to access the full research report on the Centre's website.
Also available in an electronic version via the Internet. Address as at 6 September 2011: http://www.ncver.edu.au/publications/search.html?submit_type=Search&breadth=phrase&searchwords=research+messages&criteria=title&findpubtypes=All
ISSN registration
Keywords: Adult education -- Australia -- Periodicals; Vocational education -- Australia -- Periodicals